User Interfaces in C#: Windows Forms and Custom Controls - MacDonald, Matthew (Apress, 2013)
This book represents the start of the second wave of .NET books: closely focused works that give you the insight of experienced Custom Controls takes a close look at all the ingredients you can use to design state-of-the-art application interfaces. It also framework for Windows. You don't just learn about anchoring and docking, you work with examples that show document-view controls. You also learn how to design irregularly shaped forms, unshackle data binding, and build an integrated help system. In short, this is the sort of .NET book that I would want to read as a professional developer. It's a book that goes beyond the generation of software applications. And seeing as you are reading this introduction, you've probably already realized that this